Local structural changes in colloid-polymer mixture: colloids as atomic model - Razali, Azaima; Turci, Francesco; Royall, C. Patrick (2020)
Colloidal suspension undergoes phase transition: gas, liquid and crystal states, as was observed in the phase diagram of argon atoms. Linked by these similarities, colloids have often been used as atomic models and have been given the term “designer atoms”1. The addition of polymer induces aggregation in colloidal dispersion by creating attractive interaction potential between the colloids. The addition of polymer to colloidal suspensions will cause the colloidal particles to aggregate at low volume fraction, φ2-5 forming a gel. The arrested behaviour in gels due to the polymer addition is analogous to colloidal suspensions quenching. The colloid-polymer mixture can be considered as one component system where the effective interaction is mediated by the polymer according to Asakura and Oosawa6,7 and Vrij8. In our work, we employed a well understood colloid-polymer system in order to investigate the local structural changes in reaching equilibrium ordered state. We studied the ageing of gels with different interaction strengths in experiment and simulation. Then, we also examined the effects of confinement to the sedimentation of colloids and gels. We have investigated the local structures evolution within the far from equilibrium state of gel using a confocal microscope.